Corrosion-resistant low-friction CoCrNiTiC medium-entropy alloy carbide film and preparation method thereof

CoCrNiTiC medium entropy alloy carbide film is prepared through magnetron sputtering technology, which solves the problems of poor thickness control, large internal stress and easy to fall off when used in extreme environments, and achieves good bonding between the film and the substrate and thickness control, and has excellent tribological and corrosion properties.

CN119776766APending Publication Date: 2025-04-08HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411962019.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When used in extreme environments, existing high-entropy alloy films have poor thickness control, large internal stress and easy to fall off, making it difficult to meet the high requirements for material performance in industrial applications.

Method used

Magnetically controlled sputtering technology was used to prepare CoCrNiTiC medium entropy alloy carbide film, and C atoms were introduced through solid C targets to avoid interference from H elements, achieving good bonding between the film and substrate and thickness control.

Benefits of technology

The prepared film has excellent tribological and corrosion properties, strong bonding power, fine thickness control, and is suitable for a variety of materials without contaminating the surface of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film and a preparation method thereof. The alloy comprises Co, Cr, Ni, Ti and C. The formula of the alloy comprises Co, Cr, Ni, Ti and C. A CoCrNiTiC entropy alloy carbide film is prepared on a substrate and a monocrystalline silicon wafer (100) by adopting planar radio frequency magnetron sputtering, a CoCrNi alloy target, a Ti target and a graphite target are selected as target materials, the gas introduced in the sputtering process is Ar gas with the purity of 99.99%, the working pressure is 1.0 Pa, and the deposition time is 2 hours. According to the method, the CoCrNiTiC high-entropy alloy carbide film is prepared through planar target magnetron sputtering, the thickness of the medium-entropy alloy carbide film ranges from 600 nm to 800 nm, and an SEM shows that the surface of the film is uniform and flat and has no obvious defects. Along with the increase of the carbon content, the friction coefficient of the film is gradually reduced, the corrosion resistance is enhanced, and the toughness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the field of metal material surface protection and life extension, and specifically relates to a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film and a preparation method thereof. Background technology:

[0002] Medium-entropy / high-entropy alloys, also known as multi-principal alloys, are unique in that they are composed of multiple metal elements in equiatomic or near-equiatomic proportions, and the content of each element is controlled in the range of 5% to 35%. The unique design concept of medium-entropy / high-entropy alloys gives them many excellent properties, such as high strength, high plasticity, high wear resistance, thermal stability, corrosion resistance, and oxidation resistance. However, the large amount of rare and expensive elements (such as Nb, W, Cr, V, Ni, Ti, Co, etc.) used in the alloys has indeed greatly increased their production costs, thereby limiting their wide application in industry. In order to solve this problem, researchers began to explore the feasibility of preparing high-entropy alloy films on low-cost traditional alloy substrates. This method aims to impart the excellent properties of high-entropy alloys to traditional alloys through surface modification technology, while maintaining the low-cost advantages of traditional alloys, thereby achieving a perfect combination of high performance and low cost.

[0003] At present, one of the most widely used applications of high entropy alloy films is material surface modification to achieve life extension and protection effects. As human beings continue to explore the nature, from the deep sea to the space, from the poles to the equator, all fields have put forward unprecedented challenges and demands on material performance. In extreme environments, traditional materials are often not up to the task. In the fields of machinery manufacturing, automobile industry, energy industry, aerospace, etc., mechanical parts with complex manufacturing processes and high-precision service, such as bearings, gears, couplings, connecting rods, crankshafts, etc., have put forward higher requirements on the performance of materials:

[0004] 1. It should be wear-resistant and have a small friction coefficient to reduce the wear on the substrate. Some parts such as bearings will experience high-temperature wear due to friction and heating during service, so a certain resistance to high-temperature friction and wear is required;

[0005] 2. It should have sufficient plasticity and toughness to resist impact and vibration;

[0006] 3. Since some parts need to work in a corrosive environment (such as seawater), they should have sufficient corrosion resistance. Summary of the invention:

[0007] The main purpose of the present invention is to provide a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film and a preparation method thereof to overcome the deficiencies of the prior art. The film prepared by the method has excellent tribological and corrosion properties while having good toughness. It has a wide range of applicability and can be applied to a variety of materials. The film has excellent bonding with the substrate and provides excellent thickness control capability. In addition, the preparation method can also achieve large-area coating.

[0008] A method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film is implemented by the following steps:

[0009] Step 1: Use water-abrasive sandpaper 240#, 400#, 600#, 800#, metallographic sandpaper 400#, 600#, 800# to polish the substrate on one side, and then polish it with 0.25μm diamond polishing agent. Put the polished substrate and single crystal silicon wafer into an ultrasonic cleaning machine and use petroleum ether and anhydrous ethanol for ultrasonic cleaning for no less than 15 minutes. After ultrasonic cleaning, take it out and dry it with a hair dryer for later use.

[0010] Step 2: Place the substrate and silicon wafer processed in step 1 onto the carrier plate, then install the CoCrNi alloy target, Ti:, and C target onto the corresponding DC power supply and RF power supply target positions, close the vacuum chamber, draw the background vacuum to 1×10-3Pa~3×10-3Pa, introduce Ar gas at a flow rate of 40~50sccm and maintain it unchanged, the working gas pressure is 0.5Pa~2.5Pa, apply -50V bias, the Ti target power is 40~60W, the deposition time is 10~15min, and the transition layer Ti is deposited.

[0011] Step 3: After the deposition of the transition layer is completed, turn on the power supplies of the Ti target, CoCrNi alloy target, and C target at the same time, keep the Ar gas flow rate at 40-50 sccm and unchanged, the working gas pressure at 0.5Pa-2.5Pa, apply a -50V bias, the CoCrNi alloy target power at 70-90W, the Ti target power at 40-60W, the C target power at 50-150W, and the deposition time at 100-120min to deposit a medium-entropy alloy carbide film.

[0012] The beneficial effects of the present invention are:

[0013] 1. The present invention provides a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film and a preparation method thereof to overcome the deficiencies of the prior art.

[0014] 2. Currently, laser cladding is often used as a preparation method for modifying the surface of materials using high entropy alloy coatings. However, on the one hand, the thickness of laser cladding coatings is generally thick and is not suitable for the protection of more precise parts. On the other hand, they have large internal stress and are easy to fall off. Based on this, the preparation method provided by the present invention adopts magnetron sputtering technology, has a wide range of applicability, and can be applied to a variety of materials. The film has excellent bonding with the substrate and provides excellent thickness control capabilities. In addition, the preparation method can also achieve large-area coating.

[0015] 3. Compared with other preparation methods that introduce C atoms through acetylene gas, the present invention introduces C atoms by using a solid C target, avoiding the interference of H element on the medium-entropy alloy film, and obtaining a purer medium-entropy alloy carbide film.

[0016] 4. The present invention introduces C atoms into the medium entropy alloy. On the one hand, the hardness of the film is improved through solid solution strengthening to improve its wear resistance. On the other hand, the diffusion of carbon atoms under friction makes it easy to shear contact, reducing the friction coefficient. Compared with traditional lubricating materials, the medium entropy alloy carbide film provided by the present invention not only does not pollute the material surface, but also does not cause loss due to heat generated during friction.

[0017] 5. Compared with the protective coating prepared by the existing preparation method, the medium-entropy alloy coating prepared by the present invention not only has excellent wear resistance and corrosion resistance, but also has excellent toughness and better comprehensive performance. Description of the drawings:

[0018] The accompanying drawings are included to provide a further understanding of the embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate the embodiments and are used together with the description to explain the principles of the present invention. It will be easy to recognize other embodiments and many expected advantages of the embodiments because they become better understood by reference to the following detailed description. The elements of the drawings are not necessarily to scale with each other. The same reference numerals refer to corresponding similar parts.

[0019] Figure 1 The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 1;

[0020] Figure 2 The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 2;

[0021] Figure 3The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 3;

[0022] Figure 4 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 1;

[0023] Figure 5 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 2;

[0024] Figure 6 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 3;

[0025] Figure 7 The friction coefficient of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Examples 1, 2 and 3 is

[0026] Figure 8 The impedance curves of Example 1, Example 2 and Example 3 in 3.5wt.% NaCl solution;

[0027] Fig. 9 Polarization curves of Example 1, Example 2 and Example 3 in 3.5wt.% NaCl solution;

[0028] Fig.10 The Vickers indentation morphology images of Example 1 (left picture) and Example 3 (right picture) are shown. Specific implementation method:

[0029] The following will be combined with the drawings in the experimental examples of the present invention to clearly and completely describe the technical solutions in the experimental examples of the present invention. Obviously, the experimental examples described are only part of the experimental examples of the present invention, not all of the experimental examples. Based on the experimental examples in the present invention, all other experimental examples obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] In this embodiment, a method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film is implemented by the following steps:

[0032] Step 1: Use water-abrasive sandpaper 240#, 400#, 600#, 800#, metallographic sandpaper 400#, 600#, 800# to polish the substrate on one side, and then polish it with 0.25μm diamond polishing agent. Put the polished substrate and single crystal silicon wafer into an ultrasonic cleaning machine and use petroleum ether and anhydrous ethanol for ultrasonic cleaning for no less than 15 minutes. After ultrasonic cleaning, take it out and dry it with a hair dryer for later use.

[0033] Step 2: Place the substrate and silicon wafer processed in step 1 onto the carrier plate, then install the CoCrNi alloy target, Ti:, and C target onto the corresponding DC power supply and RF power supply target positions, close the vacuum chamber, pump the background vacuum to 1×10-3Pa, introduce Ar gas at a flow rate of 45sccm and maintain it unchanged, the working gas pressure is 1.0Pa, a -50V bias is applied, the Ti target power is 60W, the deposition time is 10min, and the transition layer Ti is deposited.

[0034] Step 3: After the deposition of the transition layer is completed, turn on the power supplies of the Ti target, CoCrNi alloy target, and C target at the same time, keep the Ar gas flow rate at 45 sccm and unchanged, the working gas pressure at 1.0 Pa, apply a -50 V bias, the CoCrNi alloy target power at 75 W, the Ti target power at 60 W, the C target power at 50 W, and the deposition time at 120 min to deposit a medium-entropy alloy carbide film.

[0035] Embodiment 2: The difference between this embodiment and embodiment 1 is that the power of target C in step 3 is 100 W. The other steps and parameters are the same as those in embodiment 1.

[0036] Embodiment 3: The difference between this embodiment and embodiment 1 is that the C target power in step 3 is 150W, and the other steps and parameters are the same as those in embodiment 1.

[0037] Figure 1 The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 1;

[0038] Figure 2 The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 2;

[0039] Figure 3 The surface SEM morphology and white light interference surface roughness of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 3;

[0040] from Figure 1-Figure 3The SEM image of the film surface also shows that the surface of Example 1 is smooth and flat, and there are no steamed bun-shaped protrusions on the film surface. Steamed bun-shaped protrusions appear on the surfaces of Examples 2 and 3, and as the introduced C content increases, the particle size gradually increases and the surface roughness of the film increases.

[0041] The increase in roughness is that when the sputtering power is maintained at a low level, the bombardment of the target by Ar+ ions is weaker, resulting in a weaker atomic flow sputtered from the target surface. This reduces the atomic concentration from the target to the substrate and reduces the probability of collision between atoms. Therefore, the atoms or atomic groups reaching the substrate have higher energy retention and stronger migration ability, which is conducive to the nucleation process of the thin film.

[0042] Figure 4 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 1;

[0043] Figure 5 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 2;

[0044] Figure 6 The wear scar SEM morphology and EDS spectrum analysis diagram of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Example 3;

[0045] It can be seen from the SEM image that pits are generated on the surface of the film due to friction peeling, and the position and depth of the pits are irregular. There are no furrows inside the wear marks, which can rule out the influence of abrasive wear. Figure 4-6 The EDS spectrum shows that O atoms are enriched in the wear scar area, while the distribution of metal elements on the wear scar is uniform. In addition, the presence of Fe signals in the middle part of Example 1 and Example 2 indicates that the substrate is exposed and the film has failed. Although the EDS spectrum of Example 3 shows that elements such as Co, Cr, and Ni are lost in the wear scar area, there is no enrichment of Fe elements, and the film shows a good protective effect after wear. Since the O element in Examples 1, 2, and 3 is concentrated in the wear scar area, it is considered that the wear mechanism of the CoCrNiTiC medium entropy alloy film is oxidative wear and fatigue wear, and as the carbon content increases, the wear scar depth and wear scar width both decrease.

[0046] Figure 7 The friction coefficient of the corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film prepared in Examples 1, 2 and 3;

[0047] from Figure 7It can be seen that as the C content increases, the friction coefficient of the film shows a significant downward trend, and the wear resistance is also significantly improved under the same load. The COF value of 100r-400r represents a relatively stable state after the running-in period, and the average COF is calculated using the data of this interval. The COF curves of the films of Example 1 and Example 2 show a rapid increase at the sliding distances of 410r and 200r, respectively, indicating that the film has failed due to wear.

[0048] Figure 8 The impedance curves of Example 1, Example 2 and Example 3 in 3.5wt.% NaCl solution;

[0049] Fig. 9 Polarization curves of Example 1, Example 2 and Example 3 in 3.5wt.% NaCl solution;

[0050] A large corrosion current density indicates a faster corrosion rate. Figure 8 and Fig. 9 It can be found that Example 1 corrodes the fastest, followed by Example 2, and Example 3 exhibits better corrosion resistance. Since the CoCrNiTiC high entropy alloy film is rich in Cr and Ni elements, it will inevitably be oxidized during the corrosion process to form a passivation protective film to hinder the corrosion of corrosive ions. In addition, the addition of C element has no direct negative impact on the corrosion resistance of Cr and Ni. On the contrary, it may enhance the overall structural stability of the alloy by forming carbides, thereby indirectly improving the corrosion resistance. Therefore, it is shown that as the C content increases, the corrosion resistance of the film is effectively improved. However, this C content refers to within 20at%. If the C content is too much, on the one hand, a large amount of Cr elements in the film will be consumed, and on the other hand, a large amount of carbides will be generated, which will reduce the toughness and corrosion resistance of the film, causing local Cr deficiency and pitting.

[0051] Fig.10 The Vickers indentation morphology images of Example 1 (left picture) and Example 3 (right picture) are shown.

[0052] from Fig.10 It can be seen that circumferential cracks appeared around the indentation of the film of Example 1, and cracks appeared in the inner and radial directions of the indentation, but no film bulging phenomenon caused by the load was observed. No obvious cracks appeared in the inner, radial and circumferential directions of the indentation of the film of Example 3, indicating that the toughness of the film of Example 3 is good. The above results show that as the carbon content in the film increases, the toughness of the film increases. The high toughness of the film can prevent cracks or local brittle fractures, which is beneficial to improving the tribological properties of the film. It may be that the addition of C causes grain refinement.

Claims

1. A corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film, characterized in that: The atomic percentage of each element in the medium entropy alloy film is: Cr 19% to 27%, Co 19% to 27%, Ni 19% to 27%, Ti 11% to 15%, and C 8% to 27%.

2. The corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 1, characterized in that: The thickness of the film is 600nm~800nm.

3. The corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 1, characterized in that: The friction coefficient of medium entropy alloy carbide film is 0.15~0.

5.

4. The corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 1, characterized in that: The surface of the medium entropy alloy carbide film is dense and smooth, with a roughness Ra of <5.0nm.

5. A method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claims 1-4, characterized in that: The following steps are involved: Step 1: Pre-treatment for magnetron sputtering: use sandpaper to perform single-sided mirror grinding and polishing on the base material, then ultrasonically clean it and blow it dry for later use. Step 2: After installing the substrate material, silicon wafer, and target material, evacuate the system, introduce high-purity Ar gas, apply bias voltage, and then turn on the Ti target power supply to deposit the Ti transition layer. Step 3: Depositing a medium entropy alloy carbide film.

6. The method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 5, characterized in that: In the step 1, the single side of the base material is polished using water-abrasive sandpapers 240#, 400#, 600#, 800# and metallographic sandpapers 400#, 600#, 800# in sequence.

7. The method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 5, characterized in that: The polishing process described in step 1 is: polishing the workpiece using a 0.25 μm polishing paste for not less than 5 minutes until the surface is smooth and flat.

8. The method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 5, characterized in that: The ultrasonic cleaning described in step 1 is to first completely immerse the substrate material in petroleum ether and perform ultrasonic cleaning for no less than 10 minutes, and then use anhydrous ethanol to ultrasonically clean the substrate material to remove petroleum ether and other impurities on the substrate surface.

9. The method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 5, characterized in that: Before depositing the transition layer in step 2, the chamber background vacuum is evacuated to 1×10 -3 Pa~3×10 -3 Pa, the Ar gas flow rate is 40-50sccm and maintained unchanged, the working gas pressure is 0.5Pa-2.5Pa, a -50V bias is applied, the Ti target power is 40-60W, the deposition time is 10-15min, and the thickness of the deposited transition layer is 100-150nm.

10. The method for preparing a corrosion-resistant and low-friction CoCrNiTiC medium-entropy alloy carbide film according to claim 5, characterized in that: The CoCrNi alloy target used for depositing the CoCrNiTiC medium entropy alloy carbide film in step 3 is sintered with an equiatomic ratio, and an Ar gas flow rate of 40 to 50 sccm is introduced and maintained unchanged, the working gas pressure is 0.5Pa to 2.5Pa, a -50V bias is applied, the CoCrNi alloy target power is 70 to 90W, the Ti target power is 40 to 60W, the C target power is 50 to 150W, the deposition time is 100 to 120min, and the deposited film thickness is 600 to 800nm.

Citation Information

Cited By

  • High-entropy nano-alloy film and preparation method thereof

    CN121538611A